Conservation agriculture enhances soil and water conservation and crop yield in the Ethiopian highlands - Tilashwork Chanie Alemie; Asmare Wubet; Misganaw Fentahun; Mulugeta Worku; Abreham Awoke; Zime Ambaw; Tadele Amare; Assefa Derebe Zegeye (PLoS ONE, 2026)
Conventional tillage (CT), which is characterised by intensive soil disturbance and complete residue removal, remains the main farming system in the Ethiopian highlands. However, CT, exacerbated by climate change, has accelerated soil degradation and reduced crop productivity. Conservation agriculture (CA) is promoted as a suitable alternative to counteract these challenges, although evidence of its effectiveness remains limited in the study area. This study evaluated the impacts of CA on runoff, soil loss, infiltration rate, and crop yield by comparing four treatments such as no-tillage + mulching + intercropping (NT + M + In), no-tillage + mulching + crop rotation (NT + M + R), conventional tillage + mulching + crop rotation (CT + M + R), and conventional tillage (CT). Each treatment was implemented at a 10X10 m 2 plot, while years were considered as replications. Analysis of variance (ANOVA) at a 95% confidence level was applied using R software to evaluate the effects of treatments. The results confirmed significant differences among treatments in reducing runoff and soil loss. Compared to CT, CA practices, NT + M + R, NT + M + In, and CT + M + R reduced runoff by 71, 60, and 45% and soil loss by 88, 82, and 60%, respectively. These treatments also improved cumulative infiltration by 137, 161 and 43%, respectively. These practices also increased maize grain yield by 48, 46, and 47% and faba bean yield by 122, 321, and 91%, respectively. Overall, no-tillage combined with mulching maximised the soil and water conservation benefits of CA, thereby enhancing crop production. Therefore, CA practices, primarily, NT + M + R followed by NT + M + In, and CT + M + R are recommended for wider adoption to improve soil and water conservation, and maize and faba bean production in the study area and similar agro-ecological regions of the world.